Undecidability and the Evolution of Ideas in an Emergency Event: An Example of How to Systemically Test Organizational Effectiveness (OE) in University Groups - Romina Fucà; Serena Cubico (MDPI AG, 2020)
The location of this research is the university, through which we are progressively channeled into a seemingly insoluble Gordian knot. What is our participation in the university and what cultural and human commitments inform this participation? More trivially, what rights and duties does the individual acquire or lose within his or her academic identities? Our main target was finding an ideal organizational practice to examine, such as an emergency event. What strategy can the university adopt? Can it realign its distortions and retain its resources? How and in what ways? What information is needed for this purpose? Which actors are relevant in this process? A systemic survey model is, therefore, presented to analyze data obtained from a sample of 200 respondents from various academic groups, including students, professors, administrative staff, and other stakeholders. Quotas were used for the primary challenge posed by the pictures representing dimensions according to a systemic schema of organizational effectiveness (OE). Respondents were then asked to judge the dimensions and pictures against their personal capacity for intellectual identity, functionalism, and materialism. During the test, the participants were expected to develop their capacity to approach phenomenal consciousness and the search for its neural correlates, thereby becoming familiar with the high-order demands and challenges posed by the current information available to them. A nine-item interval behaviorally anchored rating scale (BARS) was used to develop a systemic matrix that could show the participants' collective OE when an emergency event occurs at the university. This study aims to stimulate a broader investigation into the preparation of programs and plans that should be a priority today in the context of sustainability in educational institutions, thereby setting useful thresholds on decision-making paths. To develop the collective model, a matrix generated by each respondents' dimensional modal values (DMVs) in the test and the overall samples' modal values (OMMVs) were used. Borrowing from Luce's theory of probability, we analyzed the similarity of the OE university matrix from the results in descending order, restricting our attention to modal values which were chosen for the test and demonstrate how the learning model was formulated to assume that each group with evolved behavior could respond adaptively to a conditional function thanks to its permanence in a university environment.